2020
DOI: 10.1002/joa3.12454
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of intensive atrial inflammation and fibrosis after cryoballoon ablation: PET/MRI and LGE‐MRI analysis

Abstract: Background: Atrial inflammation plays an important role in initiating atrial fibrosis, which could perpetuate atrial fibrillation (AF). However, the method of visualization of atrial inflammation has not been established. We sought to investigate whether the intensive atrial inflammation caused by cryoballoon ablation (CBA) could be detected by positron emission tomography/ magnetic resonance imaging (PET/MRI) and whether the atrial inflammation could be associated with consequent fibrosis. Methods: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, we speculate that insufficient cryo-lesion, which could be presented as lower inflammation, might be responsible for PV reconnection or reactivation of pro-arrhythmic matrix during the early phase of post-CBA. By assessment of PET/MRI, Kiuchi found that CBA induced atrial inflammation was strongly associated with lesion maturation, which could be important to the ablation success [ 17 ]. Since the inflammation after AF ablation is double-edged, optimal inflammation could consolidate the ablation lesion while lower inflammation may unmask lesion gap and consequently lead to early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that insufficient cryo-lesion, which could be presented as lower inflammation, might be responsible for PV reconnection or reactivation of pro-arrhythmic matrix during the early phase of post-CBA. By assessment of PET/MRI, Kiuchi found that CBA induced atrial inflammation was strongly associated with lesion maturation, which could be important to the ablation success [ 17 ]. Since the inflammation after AF ablation is double-edged, optimal inflammation could consolidate the ablation lesion while lower inflammation may unmask lesion gap and consequently lead to early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy though that LGE is not specific for fibrotic tissue, but can reflect other pathological processes associated with an expansion of the extracellular space such as inflammation and oedema formation, which impedes definite lesion assessment, particularly in the acute setting. [ 34 ]…”
Section: Lge-mri For the Detection Of Ablation-induced Fibrosismentioning
confidence: 99%